Magnetically stirring enhanced thermal performance of phase change material - Sun, Dao-Yu; Yan, Si-Xin; He, Zhi-Zhu (Case studies in thermal engineering, 2018)
Here we report an active method to enhance the thermal performance of phase change material (PCM) based on magnetically-stirring method. The magnetic bead with small size embedded in the container filled with octadecanol, is driven to rotate by rotating magnetic field, and induce the forced convective heat transfer of the liquid octadecanol. We investigate the impact of rotating magnetic velocity, magnetic bead size, the distance between magnetic bead and rotating permanent magnet on the surface temperature of the simulated heating plate. The experimental results indicated that magnetically stirring obviously improve the heat transfer from liquid phase to solid phase of octadecanol and make simulated heat source keep a lower and smoother temperature platform. We also find that the best condition point could be determined by matching the rotation velocity for the given size of magnetic bead. These results are expected to provide insights into the design and optimization of latent heat thermal energy storage systems. Keywords: Phase change material, Magnetically stirring, Heat transfer, Energy storage technology